The energy charts for occupants’ behavioural improvement through BIM - Roslan Rasyikin (EDP Sciences, 2021)
BIM is an easy method to design sustainable buildings for professionals like architects and engineers. By using the real measurable environment, software tools can shape building concepts such as geometry, spatial relations, geographical details and the design of structural composites and buildings, and the usage of energy annual like energy costs and life-cycle costs can be estimated and calculated. This study revealed the findings of the energy consumption within one year can provide valuable insights into the projected resources in the UNITEN Administrative Building. The application of these data would simplify energy cost calculation, an essential component of the costs of operating a property. With the purpose of maximizing energy efficiency in green buildings, the outcomes can be used as guidance to advice occupant management in optimizing occupant actions.